Complexes of (η5-Cp*)Ir(iii) with 1-benzyl-3-phenylthio/selenomethyl-1, 3-dihydrobenzoimidazole-2-thione/selenone: catalyst for oxidation and 1, 2-substituted benzimidazole synthesis. Issue 7 (27th January 2017) - Sharma, Alpesh K.; Joshi, Hemant; Bhaskar, Renu; Singh, Ajai K.
Abstract : (η 5 -Cp*)Ir(iii ) complexes catalyze at 0.01–0.1 mol%, reactions of 1, 2-phenylenediamine with ArCH2 OH and oxidation of alcohols. Abstract : The treatment of 1-benzyl-3-phenylthio/selenomethyl-1, 3-dihydrobenzoimidazole-2-thione/selenone [L1–L4 ] with [(η 5 -Cp*)IrCl(μ-Cl)]2 at 25 °C followed by NH4 PF6 results in [(η 5 -Cp*)Ir(L )Cl][PF6 ] (1–4 forL =L1 toL4 ), authenticated with high-resolution mass spectrometry (HR-MS) and multi-nuclei nuclear magnetic resonance (NMR) imaging ( 1 H, 13 C{ 1 H} and 77 Se{ 1 H}). The structures of1–4, established with single-crystal X-ray diffraction, reveal a "piano-stool" geometry around the Ir. The Ir–thio/selenoether (Ir–S/Ir–Se) bond distances (Å) are 2.347(18)–2.355(4)/2.4663(12)–2.4663(13) and Ir–thione/selenone (Ir–S/Ir–Se) distances are 2.4146(19)–2.417(2)/2.5141(16)–2.5159(12). The reaction of 1, 2-phenylenediamine with benzylic alcohols and furfuryl alcohol under mild and ambient conditions, catalyzed efficiently with complexes1–4, generates bisimine in situ . Cyclization and rearrangement via 1, 3-hydride shift triggered by its electrophilic activation with Ir(iii ) species finally results in 1, 2-disubstituted benzimidazole. The yield of the heterocycles in this one-pot synthesis is excellent to good. The aldehydes generated in situ by aerial oxidation of alcohols in the presence of1–4 as catalysts are precursors to the bisimine as the protocols of this heterocycle synthesis carried out in the absence of 1, 2-phenylenediamine give them in excellent-to-good yield. The oxidation of alcohols by hydrogen transfer to acetone was catalyzed efficiently with complexes1–4 and resulted in aldehyde/ketone in excellent-to-good yield. Each catalytic process is marginally more efficient with1 than its counterparts.